Implementasi Pembelajaran Qur’an Hadis Dengan Metode Azza Di MIN 1 Kapuas - Muhammad Iqbal Ansari; Sari Kumala; Novianti (IAI Al Khoziny Buduran Sidoarjo, 2024)
The AZZA method represents an innovative approach that addresses some of the challenges and disinterest that students may encounter when learning to read the Qur'an.Research methodology, in essence, serves as a means to gather, examine, record, and analyze data, including both primary and secondary sources, to facilitate the creation of scholarly works. In this specific study, a qualitative approach was employed, adopting the case study research method, which involves an in-depth exploration of a specific system based on extensive data collection. Following the planning stage, the next crucial step is implementation. The application of the AZZA method for Al-Qur'an Hadith learning at MIN 1 Kapuas represents an innovative departure from previous approaches.Evaluation typically occurs after implementation. Various methods are employed to assess Al-Qur'an Hadith subjects. Firstly, teachers evaluate students on a daily basis, considering aspects such as reading proficiency, memorization, and comprehension. These assessments are then recorded in the teacher's assessment book. Secondly, weekly evaluations are conducted through internal meetings involving the Al-Qur'an Hadith teachers and the Qur'an field coordinator.